Effects of attachment security priming on women’s math performance - Soares De Almeida, Antonio; Gillath, Omri; Kahalon, Rotem; Shnabel, Nurit (Frontiers in Psychology, 2023)
Activating people’s sense of attachment security can buffer against psychological threats. We tested whether security priming buffers the effects of stereotype threat among women. A pilot Study (N = 79 women, 72 men) revealed that women exposed to attachment security primes (e.g., the word ‘love’) had better math performance than women exposed to neutral primes (e.g., ‘boat’). Men’s math performance did not differ across priming conditions. Study 1 (N = 474 women) revealed that women showed better math performance in the attachment security priming condition than in the neutral or positive (e.g., ‘luck’) priming conditions. The effect was observed among women high on math identification. Study 2 was carried out online (N = 827 women). Despite the effect of security priming on the manipulation check (higher SAAM security score) security did not buffer stereotype threat effects. Theoretical and practical implications related to attachment security priming are discussed.